Effect of Rosa Mosqueta Husk Extract (Rosa rubiginosa) on Thermooxidation of Grape Seed Oil - Marcos Flores; Jaime Ortiz-Viedma; Nalda Romero; Lilia Masson; Paz Robert; Patricia Garcia (Journal of Food Quality)
There is a growing interest in lipid behavior with nutritional contribution. In this sense, it is necessary to determine the behavior of the grape seed oil during a thermooxidation process at 180°C. The induction period (OSI), together with the formation of polar compounds (CP) by HPSEC and the retention of alpha-tocopherol (AT) by HPLC, was the main parameter studied during this deterioration process. The behavior of 4 systems of oils, natural oil (a), refined oil (b), and refined oil with addition of rosa mosqueta husk extract (SGO + C) and alpha-tocopherol (SGO + AT), was compared. The results indicate that the system (a) shows a high retention of the AT content during heating. On the contrary, both systems (SGO + C and SGO + AT) presented a discrete but significant CP inhibition in relation to the values presented in purified grape seed oil (SGO). When comparing the thermooxidative behavior of the SGO + C and SGO + AT systems, it indicates better results for the first system, attributable to the combination of carotenes and AT present in C.